Predictive models of epidemiological outcomes for patients with subarachnoid hemorrhage - Galvão, Jarbas; Lima, Daniela Delwing de; Haas, Leandro José; Pereira, Eduardo Manoel (International Journal of Advanced Engineering Research and Science, 2022)
Subarachnoid hemorrhage-SAH is considered a serious disease with a high potential for mortality and disability worldwide. This study aimed to evaluate the epidemiological outcomes in patients with SAH from 2006 to 2018 through a predictive equation, considering the following variables: risk factors, early manifestations, complementary needs, neurological and systemic complications. The subjects of this study were hospitalized patients with a proven diagnosis of SAH, evaluated by the Hunt-Hess and Fisher scales and classified by the modified Rankin scale (mRS). To reach this objective, binary logistic regression was applied, with risk factors as independent variables and epidemiological outcomes as dependent. A total of 148 patients were documented, 65% female and 35% male, with a mean age of 53.7 years. Heart disease was an important predictor for the severe disability outcome, the combination of sensory impairment and syncope explained cases of death by 75.7%. Among neurological complications, hydrocephalus and vasospasm explained the severe cases and ischemic injury and rebleeding explained the death. For systemic complications, hyperglycemia and aspiration pneumonia together represented predictors for severe cases and death events, which can be explained by the presence of sepsis and fever. There is a need to intensify health prevention programs for chronic diseases and women’s health, as well as implement hospital assessment protocols.